2015
DOI: 10.1039/c5fo00533g
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight guluronate prevents TNF-α-induced oxidative damage and mitochondrial dysfunction in C2C12 skeletal muscle cells

Abstract: Muscle wasting is associated with a variety of chronic or inflammatory disorders. Evidence suggests that inflammatory cytokines play a vital role in muscle inflammatory pathology and this may result in oxidative damage and mitochondrial dysfunction in skeletal muscle. In our study, we used microwave degradation to prepare a water-soluble low molecular weight guluronate (LMG) of 3000 Da from Fucus vesiculosus obtained from Canada, the Atlantic Ocean. We demonstrated the structural characteristics, using HPLC, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
(42 reference statements)
0
6
1
Order By: Relevance
“…Blood lactate and HR responses to WAnT were not altered following cupping treatment compared to the control. Our findings somewhat contrast the purported physiological mechanisms surrounding cupping therapy, including modulating metabolic acidosis, decreased oxidative stress, enhanced mitochondrial function, and increased oxygen availability and utilization (Arce-Esquivel, et al, 2020;Dun, et al, 2015;Ekrami, et al, 2021;Hofmann, et al, 2007;Powers & Jackson, 2008;Tagil, et al, 2014). Consequently, these were plausible mechanisms that could modify the physiological responses to the anaerobic exercise, to which the present study reports no beneficial effects based on HR and lactate responses.…”
Section: Discussioncontrasting
confidence: 94%
“…Blood lactate and HR responses to WAnT were not altered following cupping treatment compared to the control. Our findings somewhat contrast the purported physiological mechanisms surrounding cupping therapy, including modulating metabolic acidosis, decreased oxidative stress, enhanced mitochondrial function, and increased oxygen availability and utilization (Arce-Esquivel, et al, 2020;Dun, et al, 2015;Ekrami, et al, 2021;Hofmann, et al, 2007;Powers & Jackson, 2008;Tagil, et al, 2014). Consequently, these were plausible mechanisms that could modify the physiological responses to the anaerobic exercise, to which the present study reports no beneficial effects based on HR and lactate responses.…”
Section: Discussioncontrasting
confidence: 94%
“…Senescence and cellular metabolism of ECM are implicated in mitochondrial dysfunction . Exposure of cells to TNF‐α induces more generation of ROS, and overproduction of ROS can result in mitochondrial dysfunction . Defective mitochondria with lower mitochondrial membrane potential can produce much reactive oxygen species (ROS), which promotes the production of intracellular malondialdehyde (MDA) that is the cell membrane lipid peroxidation product.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Exposure of cells to TNF-α induces more generation of ROS, and overproduction of ROS can result in mitochondrial dysfunction. 39,40 Defective mitochondria with lower mitochondrial membrane potential can produce much reactive oxygen species (ROS), which promotes the production of intracellular malondialdehyde (MDA) that is the cell membrane lipid peroxidation product. In the current study, we found that PD alleviated the intracellular accumulation of ROS, improved the lowered mitochondrial membrane potential and rescued the impaired ATP production in NPCs treated with TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…One previous study found that CS activity in slow‐twitch muscle is higher than that in the fast‐twitch muscle, 56 which is consistent with our findings. In addition, mitochondrial dysfunction through decreased SIRT1 expression is caused by increased levels of inflammatory cytokines generating higher levels of ROS 54,55,57 . Furthermore, ROS are produced as a by‐product of mitochondrial respiration 58 .…”
Section: Discussionmentioning
confidence: 99%